Kepakaran Perubatan Dalam Proses Mengeluarkan Fatwa Perubatan Di Malaysia: Analisa Fatwa Terpilih - Irwan Mohd Subri; Abdul Manan Ismail; Syaryanti Hussin (Universiti Sains Islam Malaysia, 2024)
This article discusses the opinions of several fatwas concerning medical issues that involved medical experts. It tries to examine the cooperation between the National Fatwa Council (Jawatankuasa Muzakarah Fatwa Kebangsaan) and medical experts in issuing certain fatwas on medical issues to see whether the views of medical experts have been taken into consideration before issuing any fatwa. The research focuses on fatwa related to medical issues that have been decided by the National Fatwa Council. The study shows that there is a close cooperation between both parties.